Dispositional mindfulness influences the balance control in elderly - Sardeli, Amanda Veiga; Sartori, César Renato; Santos, Wellington Martins; Brandão, Arthur de Freitas; Chacon-Mikahil, Mara Patrícia Traina (Journal of Innovation and Healthcare Management, 2019)
Invest higher cognitive attention to movements seems to be an important strategy for balance control and reduce fall-risk, especially during a threatened posture in elderly. The ability of pay attention in a particular way, on purpose, in the present moment, and non-judgmentally, also known as to dispositional mindfulness, seems to be one strategy to invest cognitive attention on movements and improve the balance control. The aim of our study was identify the association between dispositional mindfulness and the balance control in elderly. We evaluated the dispositional mindfulness through the Brazilian version of the Mindful Attention Awareness Scale (MAAS) and the balance capability through the balance Berg scale (BBS) in 48 elderly (age 66.3 ± 4.6, 16 males,37 females). There was significant correlation between MAAS and BBS (r= 0.32, p=0.02) and a between the semi-tandem stand balance of BBS, the most challenging test, and MAAS (r= 0.41, p=0.004). These findings evinced that the dispositional mindfulness may be one new strategy to improve the balance control and, consequently, reduce the risk of fall in elderly.